INTEGRATION OF LABOR MIGRANTS AS AN ELEMENT OF THE MIGRATION POLICY OF THE REPUBLIC OF KAZAKHSTAN - Bayandina G. D.; Altybassarova M. A.; Sartova R. B.; Mukina G.S.; Salimzhanova B. B. (Scientific Journal of Pedagogy and Economics, 2021)
The economic growth of the Republic of Kazakhstan causes an increasing need for the migrants, and the key task of the government of the Republic of Kazakhstan is to develop the measures to integrate migration resources into the national economy. The purpose of this article is to develop the priority measures, to create the conditions for the successful integration of labor migrants in the Republic of Kazakhstan. A review of the migration situation and analysis of the regional migration dynamics in the Republic of Kazakhstan showed that stable economic development and the emergence of opportunities for small business allowed Kazakhstan to become the regional center of attraction for migrant workers. At the moment, the regulatory framework, regulating internal and external migration in terms of conditions and procedures for foreign citizens’ stay in the territory of the Republic of Kazakhstan is mostly formed. The main flow of the migrant workers is made up of the citizens of Uzbekistan, Kyrgyzstan and Tajikistan, most of them work illegally and do not have social rights. Despite the measures, taken by the Government of the Republic of Kazakhstan to adapt and integrate labor migrants, the problems of their awareness, regarding employment, social protection, pension provision, and limited access to health services are quite acute. Taking into account the identified problems, measures of the state integration policy should include: information support for potential migrants in the framework of pre-departure events; creating conditions for improving the language competence of migrants and ensuring the portability of social rights of migrants, in particular, ensuring the mobility of the pensions within the framework of the integration Association of the EAEU.